2006
DOI: 10.3797/scipharm.2006.74.209
|View full text |Cite
|
Sign up to set email alerts
|

Development of bioadhesive chitosan gels for topical delivery of lidocaine

Abstract: Lidocaine (LC) is a local anesthetic agent. The aim of this study is prolonging the anesthetic effect of this drug for transdermal delivery. Gels of LC hydrochloride were prepared with three different molecular weights (MW) and concentrations of chitosan. lecithin was used as permeation enhancer. Viscosity, bioadhesion, drug release from synthetic membranes, drug permeation through the biological barrier (rat skin) and antinocicetive effect of gels were studied. Increasing the concentration of chitosan caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 19 publications
0
28
0
2
Order By: Relevance
“…In a previous study, Foda et al (26) reported that the release of tramadol HCl from L-CH sponges was slower than from H-CH sponges because smaller pore sizes were evident in L-CH sponges compared to sponges prepared by higher grades of chitosan. In another study, Varshosaz et al (39) stated that the release of lidocaine from uncross-linked chitosan films increased as the molecular weight of chitosan increased. Lidocaine release from L-CH films was slower than that from M-CH films, and the highest release was obtained from H-CH films.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Foda et al (26) reported that the release of tramadol HCl from L-CH sponges was slower than from H-CH sponges because smaller pore sizes were evident in L-CH sponges compared to sponges prepared by higher grades of chitosan. In another study, Varshosaz et al (39) stated that the release of lidocaine from uncross-linked chitosan films increased as the molecular weight of chitosan increased. Lidocaine release from L-CH films was slower than that from M-CH films, and the highest release was obtained from H-CH films.…”
Section: Discussionmentioning
confidence: 99%
“…Although their size causes a challenge in utilizing them as a human food, the shell and minced meat of green crabs have potential for utilization by the food industry. The crustacean exoskeleton contains chitin, which has a wide range of applications in industries such as food and agriculture, cosmetics, nutraceuticals, pharmaceuticals and textiles . Many applications for crab shell derivatives have been reported in the scientific literature, whereas there are a limited number of studies on minced crab meat and its potential application in food products.…”
Section: Introductionmentioning
confidence: 99%
“…There are several pharmaceutical dosage forms of lidocaine HCl available on the market, i.e., solution for injection or infusion, nasal spray, oral gel and transdermal patch [24,26]. Several authors have developed the buccal mucoadhesive systems of lidocaine and/or lidocaine HCl [25,[27][28][29]. However, in previous literature, no attempt has been taken to formulate lidocaine HCl buccal patches simply using PVA and PVP along with Eudragit S100.…”
Section: Introductionmentioning
confidence: 99%